A DNA Barcode‐Based Aptasensor Enables Rapid Testing of Porcine Epidemic Diarrhea Viruses in Swine Saliva Using Electrochemical Readout. (9th June 2022) - Victorious, Amanda; Zhang, Zijie; Chang, Dingran; Maclachlan, Roderick; Pandey, Richa; Xia, Jianrun; Gu, Jimmy; Hoare, Todd; Soleymani, Leyla; Li, Yingfu
Abstract: Pen‐side testing of farm animals for infectious diseases is critical for preventing transmission in herds and providing timely intervention. However, most existing pathogen tests have to be conducted in centralized labs with sample‐to‐result times of 2–4 days. Herein we introduce a test that uses a dual‐electrode electrochemical chip (DEE‐Chip) and a barcode‐releasing electroactive aptamer for rapid on‐farm detection of porcine epidemic diarrhea viruses (PEDv). The sensor exploits inter‐electrode spacing reduction and active field mediated transport to accelerate barcode movement from electroactive aptamers to the detection electrode, thus expediting assay operation. The test yielded a clinically relevant limit‐of‐detection of 6 nM (0.37 μg mL −1 ) in saliva‐spiked PEDv samples. Clinical evaluation of this biosensor with 12 porcine saliva samples demonstrated a diagnostic sensitivity of 83 % and specificity of 100 % with a concordance value of 92 % at an analysis time of one hour. Abstract : A rapid, simple, and reagent‐less dual‐electrode electrochemical chip (DEE‐Chip) was developed using a barcode‐releasing electroactive aptamer for on‐farm detection of porcine epidemic diarrhea viruses (PEDv). This biosensor demonstrated a diagnostic sensitivity of 83 % and specificity of 100 % using 12 porcine saliva samples with a concordance value of 92 % at an analysis time of one hour.